Mechanistic synthesis of a sequential calcium-carboxylate-based linker (Ca-MOFs) and rapid assessment of chemical stability through XRD analysis - Roslan, Muhammad Qusyairi Jori; Aris, Ahmad Zaharin; Abdul Rahman, Mohd Basyaruddin; Ngee, Lim Hong; Mohd Isa, Noorain; Ahmad Aljafree, Nurul Farhana (Elsevier, 2024)
Many MOFs based on various metal ions including s-, p-, d-, and f-block elements have been developed over the past decade. Despite their abundance, low cost, and non-toxicity, s-block MOFs have been explored less frequently than those based on transition metals and f-block metal ions. Sequential calcium carboxylate-based linker MOFs (Ca-MOFs) were successfully synthesized and constructed using a solvothermal system and coordination bonding. Sequential Ca-MOFs were subjected to 13 different environments to thoroughly examine their framework stability. The investigation demonstrated a calcium-carboxylate-based linker possessing superior robustness towards hydrolysis, Brønsted–Lowry acid–bases, and polarity stability from crystallite modification through the XRD spectrum before and after exposure. In this study, the Ca-H2BDC framework was found to be highly chemically stable with almost no observed crystallite modifications. The stability of sequential calcium-carboxylate-based linker MOFs reflects strong coordination bonding according to the hard soft acid base (HSAB) principle.